(untitled) (Fiep Bulletin - online, 2014)
The understanding of the meaning of the word culture is as plural as the number of those that try to define it. It is the synthesis of the history of one determined society in all its expressions. It is at the same time an inheritance that man receives when being born and is a man’s creation. The habits, ideas, institutions, language, instruments and material workmanships of a group express its culture. This inheritance, that the man receives when being born, is a dynamic patrimony, permanently modified by the members of the group or by members of other groups, for reasons of geographic displacement of the populations, related to, for example, climatic factors, politics related dominations, search of better conditions of life, among others. The Sport Culture can be modernly considered a branch of the science of the culture since it is the consequence of the theoretical and academic effect of the growth and the development of social sciences and sciences of the culture in the practical area, in the representations area and the sports myths, that are differentiated according to the countries and social groups. It searches the description and interpretation of a universe of practical activities, techniques and symbols, which importance is undeniable in modern society. The Rhythmic Gymnastics is able to harmonize and to contextualize diversified expressions and artistic activities. Each one contributes with its portion to the essence of Arts related to the idealized movements, felt and transformed into feelings of subliming of the ego. It is intended, in this work, to proceed to an analysis of the Rhythmic Gymnastics using the existing specific bibliography on the subject, beyond other sources of interest and to trace parallels with the experience of thirty years of the author related to this modality, particularly as the responding coach for competitive teams since the beginning levels until the highest levels of excellence as, for example, of gymnasts of international level, also licensed for the FIG.